Perceptions of, and attitudes towards, English teaching and learning in Cameroon’s technical education - Innocent Mbouya Fasse; Alain Flaubert Takam (Institute of Advanced Engineering and Science, 2022)
This study examined the current practices, difficulties and impacts of English as second official language (ESOL) teaching and learning in secondary schools in Cameroon. It investigated the perceptions and attitudes of students, teachers and parents towards the teaching and learning of ESOL, including prevailing teaching and learning practices. This study stemmed from the observation that the exit profile of most students in technical secondary schools does not correspond to the official exit profile set out by the Ministry of Secondary Education (MINESEC). It was therefore necessary to survey students, parents, and teachers with the goal of identifying areas of concern and proposing remedial solutions. Responses of these key stakeholders selected in four education institutions (including two technical high schools and two general high schools) to questionnaires have provided data for the study. Such responses offered insights into the current situation in Cameroon’s ESOL, as well as into the possible utility of, and desire for, the development of ESOL courses aimed at students learning in technical schools. The inclusion and development of English for specific purposes (ESP) in Cameroon’s ESOL teaching and learning could help bring education stakeholders and policymakers closer to what they want to see from the country’s ESOL program.